Распознавание зрительных образов на основе топологической обработки информации - Demyokhin, V. V.; Danilov, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
A method and device for image classification have been developed, enabling determination of the class membership of visual patterns. The method is based on changes in the topology of stochastic connections between sensors and associative elements (A-elements), which depend on the distribution of brightness levels at the input of the recognition system and the distribution of reflective (transmissive) states of the A-element matrix established during training.